The Role of Islamic Religious Education Teachers in Internalizing Islamic Values to Prevent Bullying at SMPN 5 Sukoharjo - Ilham Ahmad Rifai; Zaenal Abidin (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to describe the role of Islamic Religious Education (Pendidikan Agama Islam/PAI) teachers in preventing bullying behavior at SMPN 5 Sukoharjo. Bullying remains a serious problem in the school environment, occurring in verbal, nonverbal, social, and physical forms, and has negative impacts on students’ psychological development and character formation. This research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation involving PAI teachers, guidance and counseling teachers, homeroom teachers, and students. The findings indicate that PAI teachers play a strategic role in bullying prevention by integrating Islamic values into the learning process, fostering the habituation of noble character, providing role modeling, and delivering Qur’anic and Hadith-based teachings that emphasize the prohibition of harming or humiliating others. In addition, PAI teachers collaborate with guidance and counseling teachers, maintain intensive communication with parents, and optimize religious activities such as Qur’an recitation (tadarus), Dhuha prayer, the recitation of Asmaul Husna, and other religious habituation programs. These efforts contribute to reducing bullying behavior and fostering students’ character to become more empathetic, polite, and respectful toward others. Therefore, Islamic religious education serves as an important instrument in creating a safe, religious, and bullying-free school environment.